ANALISIS OPTIMALISASI PERAN KOMITE SEKOLAH DALAM MENDUKUNG PROGRAM-PROGRAM SEKOLAH - Husain, Rusmin; Zubaidi, Mohamad; Nanda, Ni Luh Ray Satya; Rouf, Mardiana Farida; Gobel, Jovita Putri; Amain, Putri Jahwana; Supriadin, Supriadin (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
The quality of education is not solely dependent on school performance but also significantly influenced by collaborative efforts between the school and the community. This study aims to explore the role of the school committee in supporting thematic programs at SDN 6 Tapa, Bone Bolango Regency, using a qualitative case study approach. Findings reveal that the school committee plays more than an administrative role; it actively participates in implementing programs such as Child-Friendly Schools, Healthy Schools, and Inclusive Schools. The committee's involvement includes providing financial support, participating in activities, and facilitating communication between the school and parents. All committee members, from chairperson to treasurer, demonstrate proactive and responsive participation aligned with school needs. Regular coordination mechanisms through letters, digital messaging, and face-to-face meetings strengthen a synergistic partnership. This study contributes valuable insights into collaborative practices within primary education settings, especially in non-urban areas that often face resource limitations. The holistic and participatory approach presents a potential collaboration model that can be adapted in other school environments. ABSTRAKKualitas pendidikan yang optimal tidak hanya bergantung pada performa institusi sekolah, melainkan juga pada kekuatan kolaboratif antara sekolah dan masyarakat. Penelitian ini bertujuan mengkaji secara mendalam peran komite sekolah dalam mendukung program-program tematik di SDN 6 Tapa, Kabupaten Bone Bolango, dengan pendekatan studi kasus kualitatif. Temuan menunjukkan bahwa komite sekolah tidak sekadar hadir dalam peran administratif, melainkan terlibat aktif dalam pelaksanaan program seperti Sekolah Ramah Anak, Sekolah Sehat, dan Sekolah Inklusif. Keterlibatan komite terwujud dalam bentuk dukungan dana, partisipasi kegiatan, hingga fasilitasi komunikasi antara sekolah dan orang tua. Seluruh struktur komite, mulai dari ketua hingga bendahara, menunjukkan partisipasi yang proaktif dan responsif terhadap kebutuhan sekolah. Mekanisme koordinasi yang dibangun secara rutin melalui surat, pesan digital, maupun pertemuan langsung memperkuat kemitraan yang sinergis. Penelitian ini memberikan kontribusi penting dalam memperkaya wawasan praktik kolaboratif di satuan pendidikan dasar, khususnya pada konteks wilayah non-perkotaan yang seringkali dihadapkan pada keterbatasan sumber daya. Pendekatan holistik dan partisipatif ini menawarkan model kerja sama yang potensial untuk direplikasi di lingkungan sekolah lain.